The bowed string as the two-terminal oscillator - BUDZYŃSKI, Gustaw; KULOWSKI, Andrzej (Archives of Acoustics, 1977)
The paper presents a method of the evaluation of the shape of bowed string oscillations. The method employs the analogy between the bowed string and the electrical, two-terminal oscillator. The velocity-dependent friction force between string and bow, investigated experimentally many years ago, was applied as a stimulating function of the oscillator. The evaluated shapes and amplitudes are in good agreement with experimental results.